EFFLUENT TREATMENT OF PHARMACEUTICAL INDUSTRY BY USING SUBSURFACE FLOW WETLAND SYSTEM - Mega Anggraeni; Henna Rya Sunoko; Hadiyanto Hadiyanto (Diponegoro University, 2014)
Constructed wetland is one of the alternatives to increase water quality before it flowed into waterways. Sub Surface Flow Wetland System is one type of the constructed wetland for waste water treatment which is using symbiotic relation between water plants and microorganism around rooting system (rhizosphere) in media. Cyperus alternifolius and Canna indica, L. as well as gravel and sand media are plants and medias that can be used in constructed wetland. This research aimed to analyze the effectiveness of plant species between Cyperus alternifolius and Canna indica, L. as well as the effectiveness of gravel and sand media to decrease nitrite, ammoniak, BOD, and COD concentrations. Four reactors SSF-Wetlands with dimension of 120 cm x 30 cm x 50 cm were used in this research. The study was conducted over 12 days following the acclimatization of plants for 7 days. Data analysis were performed by comparing the degradation coefficient (k) of BOD, COD, nitrite, and ammonia concentrations with retention time of the effluent. The results showed that the degradation rate for the reactor with with gravel media and Cyperus alternifolius for nitrite variable was 0.60, ammonia 0.49, BOD 0.45, and COD 0.36. Cyperus alternifolius have a higher effectiveness in reducing the concentration of nitrite, ammonia , BOD and COD than Canna indica , L. Reactors with gravel media have higher effectiveness in reducing BOD , COD , ammonia and nitrite concentration than sand media. Keywords : Canna indica. L. , Cyperus alternifolius, SSF - Wetland, , WWTP effluent of pharmaceutical industry